Discrimination of Minority Ethnic Chinese in Film “Ngenest” by Ernest Prakarsa : A Sociolinguistics Study - Hasma Rahmat Gundala; Puspita Sari (Universitas Cokroaminoto Palopo, 2022)
The title of the study is Discrimination Minority Ethnic Chinese In Film